Development of an Inquiry-Based e-LKPD High School Science on the Topic of Pressure to Improve Scientific Literacy - Wendy Rahmawan; Sabar Nurohman; Nur Ainun; Novia Budiarti (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
The low scientific literacy of Indonesian students, as reported by PISA and the 2023 ANBK at SMP Negeri 3 Samalantan, is driven by abstract, teacher-centered science instruction on the topic of Pressure. This study aims to develop and evaluate the feasibility, practicality, and effectiveness of an Inquiry Learning-based Electronic Student Worksheet (e-LKPD) to improve students' scientific literacy. This Research and Development (R&D) study applied the ADDIE model. Data were collected using validation sheets, response questionnaires, and OECD-aligned scientific literacy pretests/posttests. The results showed that the e-LKPD is highly feasible based on content (80%), syntax construction (78%), and language (82%) evaluations. It was also deemed highly practical due to interactive multimedia elements that foster independent learning via devices. In the limited-scale trial, the students' average score increased significantly from 36 to 65 ($0.000 < 0.05$). In the large-scale trial, the inquiry e-LKPD group achieved a higher score increase (37.12 to 58.85) than the conventional group (32.14 to 43.33). The MANOVA test ($0.002 < 0.05$) confirmed that integrating structured scientific investigations and real-world phenomena (e.g., submarines and hydraulic brakes) is significantly superior in enhancing scientific reasoning compared to standard methods. In conclusion, this e-LKPD is an effective instructional innovation to transition from passive to active, student-centered learning.